2022
DOI: 10.1111/bcp.15579
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of methotrexate polyglutamates in relation to efficacy and toxicity of methotrexate in inflammatory arthritis, colitis and dermatitis

Abstract: In immune-mediated inflammatory diseases (IMIDs), early symptom control is a key therapeutic goal. Methotrexate (MTX) is the first-line treatment across IMIDs. However, MTX is underutilized and suboptimally dosed, partly due to the inability of making individualized treatment decisions through therapeutic drug monitoring (TDM). To implement TDM in clinical practice, establishing a relationship between drug concentration and disease activity is paramount. In this meta-analysis, we investigated the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 74 publications
3
25
1
Order By: Relevance
“…Several studies suggested that intracellular levels of MTX-PGs in RBCs predicted MTX (non-)response in patients with RA 2 10–12 17 18 21 22. This was confirmed in a recent meta-analysis performed by our group 23. Although MTX-PGs analysis in RBCs fulfils the requirements of a TDM tool by measurements using a validated method, showing interindividual variation and a relationship with efficacy, RBCs may not be the optimal cell type for TDM of MTX as they are not primary involved in RA disease pathogenesis 11 12 22 24.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Several studies suggested that intracellular levels of MTX-PGs in RBCs predicted MTX (non-)response in patients with RA 2 10–12 17 18 21 22. This was confirmed in a recent meta-analysis performed by our group 23. Although MTX-PGs analysis in RBCs fulfils the requirements of a TDM tool by measurements using a validated method, showing interindividual variation and a relationship with efficacy, RBCs may not be the optimal cell type for TDM of MTX as they are not primary involved in RA disease pathogenesis 11 12 22 24.…”
Section: Introductionsupporting
confidence: 77%
“…RBC MTX-PG 4-5 at month 1 are associated with lower disease activity measured by DAS28 over a period of 6 months (online supplemental table S2B). However, this study was not powered to detect associations with disease activity, which were clearly found for RBC MTX-PGs in previous studies and a meta-analysis 11 23…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In previously performed meta-analysis, we showed that RBC MTX-PGs might be useful to monitor drug treatment response. 7 As several laboratories have described methods to measure intracellular MTX-PGs, this may be become a biomarker that will be generally available in clinical routine. Although other studies advised that MTX-PG total should be at least 20 and preferably above 60 nmol/L at steady-state, 13,[27][28][29] clear cutoffs for therapeutic drug monitoring (TDM) were missing.…”
Section: Articlementioning
confidence: 99%
“…Lower FPGS activity and subsequent inefficient polyglutamylation is a well-known phenomenon associated with a rapid efflux of MTX from cells 11. MTX-PG have been detected in several human cells such as erythrocytes or peripheral blood mononuclear cells (PBMCs) and low levels of MTX-PG have been associated with increased resistance to therapy 12 13. In this regards, recent molecular studies have shown that a significant reduction of FPGS activity is associated with aberrant pre-mRNA splicing of this enzyme, including partial retention of intron 8 (8PR) and a higher ratio of FPGS 8PR over FPGS wild type (WT) 14.…”
Section: Introductionmentioning
confidence: 99%